2022
DOI: 10.1021/acs.jafc.1c06998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee against MPTP-Induced Motor Deficits and Neurodegeneration in Mice Via Regulating Gut Microbiota

Abstract: The mechanisms of coffee against Parkinson disease (PD) remained incompletely elucidated. Numerous studies suggested that gut microbiota played a crucial role in the pathogenesis of PD. Here, we explored the further mechanisms of coffee against PD via regulating gut microbiota. C57BL/6 mice were intraperitoneally injected with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to induce a PD mouse model, then treated with coffee for 4 consecutive weeks. Behavioral tests consisting of the pole test and beam-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Furthermore, previous studies have reported that coffee contains possible neuroprotective compounds such as caffeine and neuroprotective polyphenols (122,123). Coffee can ameliorate motor deficits and dopaminergic neuronal loss, and reduce a-synuclein aggregation in MPTP-induced mice via regulating gut microbiota (124). Coffee can increase the level of anti-inflammatory Bifidobacteria and decrease the levels of Clostridium spp.…”
Section: A-synuclein Pathologymentioning
confidence: 99%
“…Furthermore, previous studies have reported that coffee contains possible neuroprotective compounds such as caffeine and neuroprotective polyphenols (122,123). Coffee can ameliorate motor deficits and dopaminergic neuronal loss, and reduce a-synuclein aggregation in MPTP-induced mice via regulating gut microbiota (124). Coffee can increase the level of anti-inflammatory Bifidobacteria and decrease the levels of Clostridium spp.…”
Section: A-synuclein Pathologymentioning
confidence: 99%
“…It also suggested that CL might alleviate cognitive impairment in the PD model by improving DA neuron damage. However, the main culprit behind the death of DA neurons in PD patients is the abnormal accumulation of α-syn. , To better understand the role of CL-intervention in the deposition of α-syn, another strain NL5901, expressing age-related α-syn together with GFP in vivo, was used to detect α-syn accumulation. As shown in Figure F, CL reduced the number of α-syn aggregates in NL5901.…”
Section: Resultsmentioning
confidence: 99%
“…Motor dysfunction was confirmed using rotarod and pole tests in MPTP-induced PD mice, consistent with previous reports. [65][66][67] The loss of DA neurons leads to reduced dopamine, which is responsible for motor dysfunction in PD patients. 68 TH, a marker of DA neurons, is an enzyme necessary for the synthesis of dopamine.…”
Section: Food and Function Papermentioning
confidence: 99%
“…[4][5][6] Under the stimulation of α-SYN accumulation and neurotoxins such as MPTP, mitochondrial apoptosis is triggered, leading to the loss of DA neurons. 7 Therefore, apoptosis is one of the important pathogenesis factors of PD. Moreover, neuroinflammation is another contributor that causes or aggravates PD.…”
Section: Introductionmentioning
confidence: 99%